CLINICAL PROFILE AND SURVIVAL IN PATIENTS WITH HIGH-GRADE NON-HODGKIN LYMPHOMA - ACC Farias; FET Filho; IL Pontes; LA Gurgel; FAC Silva; RM Ribeiro; DS Oliveira; RS Andrade (Hematology, Transfusion and Cell Therapy)
Objectives: This study aims to compare clinical parameters and outcomes between patients with high grade non-Hodgkin lymphomas undergoing intensive chemotherapy schedules. Material and methods: This cross-sectional study included patients diagnosed with High grade non-hogdkin lymphomas (HGNHL) and Burkitt's lymphoma (BL) treated at Hospital Geral de Fortaleza. The treatment regimen was R-CODOX-M/R-IVAC. Data were collected on various clinical parameters, including age, time to chemotherapy, haemoglobin (Hb), white blood cell count (Wbc), neutrophils (Neut), lymphocytes (Linf), platelet count (Plaq), creatinine (Cr), urea (Ur), and lactate dehydrogenase (LDH). Variables were summarised using medians and interquartile ranges (IQR). Comparisons between groups were evaluated using non-parametric tests, specifically the Mann-Whitney U-test, with p-values < 0.05 considered statistically significant. Overall survival (OS) was assessed using the Kaplan-Meier method, with a 95% confidence interval and p-values < 0.05 deemed statistically significant. Results: Between 2021 and 2024, 11 patients were diagnosed with high-grade non-Hodgkin lymphoma. The median age of the patients was 26 years, with an interquartile range (IQR) from 25.0 to 44.5 years. The time from diagnosis to admission at the Hospital Geral de Fortaleza (Time_dx_to_hgf) varied considerably, with a median of 19 days and an IQR from -10.5 to 36.5 days, indicating a wide range of delays and some instances of early intervention. The time from diagnosis to the initiation of treatment (Time_dx_treat) had a median of 48 days, with an IQR from 29.5 to 66.5 days, reflecting the varied timelines in starting therapy. The number of hospitalisations (N_internation) had a median of 3, with an IQR from 2.00 to 4.50, indicating the frequency of inpatient care required for these patients. The follow-up time in months (Time_months) showed a median of 9.33 months, with an IQR from 5.38 to 15.7 months, highlighting the duration over which these patients were monitored. The OS was 27.5% in two years, with no difference between HIV positive patients (p-value > 0,05). Discussion: The analysis reveals significant variability in clinical presentation and timing of treatment among patients with high-grade non-Hodgkin lymphoma and Burkitt lymphoma. Despite the urgent need for prompt intervention in these high-proliferative lymphomas, the median time to treatment initiation was 48 days, suggesting delays that could negatively impact outcomes. The overall survival rate of 27.5% at two years underscores the aggressive nature of these diseases. The lack of significant differences in survival between HIV-positive and HIV-negative patients indicates that timely and intensive treatment is crucial for all patients, regardless of HIV status. The study highlights the necessity for immediate and aggressive therapy to improve survival rates in these high-grade lymphomas. Conclusion: There are considerable variability in clinical presentation and timing of treatment among patients with high-grade lymphoma and Burkitt lymphoma. The time to iniate treatment was extremely harmful and this group of high proliferative lymphoma must start intensive treatment as soon as possible.